MENGUATKAN PSYCHOLOGYCAL WELL-BEING KONSELOR DENGAN PRAKTIK PERILAKU SUFI AMALI - Casmini Casmini; Firda Amrina Fitri; Faiz Muaddibi (Universitas Islam Negeri Mataram, 2020)
This aims to explore the efforts of counselors in strengthening their personality that is characterize by psychological well-being (PWB) by practicing the values contained in Sufism. The study is a qualitative literature study using a transpersonal psychology approach. The results of the study describe that counselors with psychological well-being characters can synergize intellectual, emotional, and spiritual competence. Efforts are being made to character PWB by appling the values of Sufism amali, namely the devine value, insaniyah and around the globe. Behavior practices conducted by the counsellor are wara’, repentance, praying, dhikr, praying tahajjud, and fasting 6 days in Shawwal, spending wealth in the way of Allah, making friends with the needy and poor and istiqomah in His way. The practice of Sufism practiced by the counsellor has implications for the personality aura of the counselor that becomes a habit in the pre, during, and post counselling services